2011
DOI: 10.1071/ch11054
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Extension of the Non-Nucleoside Reverse Transcriptase Binding Pocket

Abstract: Superimposition of 125 non-nucleoside inhibitors from human immunodeficiency virus reverse transcriptase structures reveals a novel binding space deeper into the enzyme for some of these inhibitors, allowing access to the polymerase active site. This may enable us to design new inhibitors of this enzyme with better mutation resistance profiles. We have analysed this new binding space and have docked our in-house scaffolds into this region, highlighting the possibility of the formation of new hydrogen bonds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This compound inhibited HIV-1 replication with an EC 50 value of ∼38 nM. 22 Given our ongoing interest in the development of HIV inhibitors 23,24,[27][28][29] and the renewed vigour for the development of next generation IN inhibitors, we conducted a screening program utilising a number of 'in-house' compound libraries from which an O-allyltyrosine-based tripeptide (compound 6, Fig. 3) was identified to inhibit IN with an IC 50 value of 17.5 μM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound inhibited HIV-1 replication with an EC 50 value of ∼38 nM. 22 Given our ongoing interest in the development of HIV inhibitors 23,24,[27][28][29] and the renewed vigour for the development of next generation IN inhibitors, we conducted a screening program utilising a number of 'in-house' compound libraries from which an O-allyltyrosine-based tripeptide (compound 6, Fig. 3) was identified to inhibit IN with an IC 50 value of 17.5 μM.…”
Section: Introductionmentioning
confidence: 99%
“…This compound inhibited HIV-1 replication with an EC50 value of ~38 nM. Given our ongoing interest in the development of HIV inhibitors 23,24,[27][28][29] and the renewed vigour for the development of next generation IN inhibitors, we conducted a screening program utilising a number of 'in-house' compound libraries from which an O-allyltyrosine-based tripeptide (Compound 6, Figure 3) was identified to inhibit IN with an IC50 value of 17.5 µM. This tripeptide, which emerged from our ongoing antibacterial drug design program,30-32 presented as an appealing scaffold for drug development endeavours since: a) analogues could be rapidly accessed via standard peptide coupling approaches, b) the scaffold is amenable to diverse structural and functional group alterations and c) the tripeptide bears no significant structural similarity to any currently reported peptide-based integrase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The former of these two papers came from Renate Griffith and co-workers (University of New South Wales and University of Wollongong, Australia). [1] In the short communication, they report on a recent discovery of an under-used binding area, which allows access to the active site of HIV reverse transcriptase (RT) and may lend itself to the design of new inhibitors with a better resistance profile. They have used molecular docking to investigate this little-used expansion of the very well known RT binding pocket and have shown that the studied compounds can potentially access this novel binding space.…”
mentioning
confidence: 99%
“…Two contributions deal with drug design issues for HIV, looking at it from therapeutics [1] and vaccine [2] development points of view. The former of these two papers came from Renate Griffith and co-workers (University of New South Wales and University of Wollongong, Australia).…”
mentioning
confidence: 99%